Re-writing knowledge, re-design textbooks: auto-production of contents in the classroom - Anichini, Alessandra; Parigi, Laura (Educar em Revista, 2019)
This contribution is a report of a qualitative research carried out within the Avanguardie Educative project aimed at describing and analyzing the experience of a group of Italian teachers in relation to the practice of textbook and digital resources auto-production. The research, conducted with some schools involved in an experimentation process of the alternative adoption of the textbook, has allowed us to start an in-depth reflection on the motivations that induce teachers to opt for this choice, in the direction of a rereading the relationship between curriculum, National Indications and teaching autonomy, with particular attention to the student considered an active subject of his / her training.